Komunikasi Islam dan Tantangan Penyebaran Informasi di Media Digital - Neng Ayu Saadah (4, 2026)
The development of digital media has brought about significant changes in societal communication patterns, including the dissemination of religious information. Digital media provides extensive opportunities for Islamic communication to convey da'wah, educational, and moral values ​​to the public quickly and effectively, without the constraints of time and space. However, this development also presents various challenges, such as the spread of hoaxes, hate speech, disinformation, low digital literacy, and a decline in communication ethics in the digital space. This study aims to analyze Islamic communication and the challenges of disseminating information in digital media, as well as to examine the importance of applying Islamic communication principles in addressing the dynamics of information technology development. This study employed a qualitative method with a descriptive approach through library research. Data were obtained from various sources, such as books, scientific journals, articles, and documents relevant to Islamic communication and digital media. Data analysis techniques included data reduction, data presentation, and systematic drawing of conclusions. The results indicate that digital media plays a strategic role as a means of da'wah and the dissemination of Islamic information in a broader, interactive, and innovative way. However, the use of digital media without ethical and responsible practices can have various negative impacts on society. Therefore, Islamic communication principles such as honesty, tabayyun (religious dialogue), politeness, and social responsibility are crucial for communication activities on digital media. By implementing these values, digital media can be utilized as a means of building a knowledgeable, moral, tolerant, and harmonious society amidst increasingly rapid technological developments. Abstrak Perkembangan media digital telah membawa perubahan besar dalam pola komunikasi masyarakat, termasuk dalam penyebaran informasi keagamaan. Media digital memberikan peluang yang luas bagi komunikasi Islam untuk menyampaikan nilai-nilai dakwah, pendidikan, dan moral kepada masyarakat secara cepat dan efektif tanpa batas ruang dan waktu. Namun, di sisi lain, perkembangan tersebut juga menghadirkan berbagai tantangan, seperti penyebaran hoaks, ujaran kebencian, disinformasi, rendahnya literasi digital, serta menurunnya etika komunikasi di ruang digital. Penelitian ini bertujuan untuk menganalisis komunikasi Islam dan tantangan penyebaran informasi di media digital serta mengkaji pentingnya penerapan prinsip-prinsip komunikasi Islam dalam menghadapi dinamika perkembangan teknologi informasi. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif melalui studi kepustakaan (library research). Data diperoleh dari berbagai sumber seperti buku, jurnal ilmiah, artikel, dan dokumen yang relevan dengan komunikasi Islam dan media digital. Teknik analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan secara sistematis. Hasil penelitian menunjukkan bahwa media digital memiliki peran strategis sebagai sarana dakwah dan penyebaran informasi Islam yang lebih luas, interaktif, dan inovatif. Akan tetapi, penggunaan media digital yang tidak disertai etika dan tanggung jawab dapat menimbulkan berbagai dampak negatif bagi masyarakat. Oleh karena itu, prinsip komunikasi Islam seperti kejujuran, tabayyun, kesantunan, dan tanggung jawab sosial sangat penting diterapkan dalam aktivitas komunikasi di media digital. Dengan penerapan nilai-nilai tersebut, media digital dapat dimanfaatkan sebagai sarana membangun masyarakat yang berilmu, berakhlak, toleran, dan harmonis di tengah perkembangan teknologi yang semakin pesat.